2013
DOI: 10.1177/0969733013500163
|View full text |Cite
|
Sign up to set email alerts
|

Can quality from a care ethical perspective be assessed? A review

Abstract: Three promising qualitative instruments were found, which follow the logic of the patient and take their specific context into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 75 publications
(74 reference statements)
0
16
0
1
Order By: Relevance
“…Ethical theories have been used to assess quality of care (Kuis, Hesselink and Goossensen 2014) but have focused on measuring care which has in itself been argued to be ethically problematic (Nagington, Luker and Walshe 2013). This study utilises poststructural theory to shape an understanding of quality care as ethical care without relying on measurement.…”
Section: Quality Care As Ethical Carementioning
confidence: 99%
“…Ethical theories have been used to assess quality of care (Kuis, Hesselink and Goossensen 2014) but have focused on measuring care which has in itself been argued to be ethically problematic (Nagington, Luker and Walshe 2013). This study utilises poststructural theory to shape an understanding of quality care as ethical care without relying on measurement.…”
Section: Quality Care As Ethical Carementioning
confidence: 99%
“…Die affektive Natur, (latente) Einstellungen und das Moralverständnis einer Person gelten als schwer messbare Konstrukte, die in der Überprüfung der Pflegequalität bislang kaum eine Rolle spielen (Kuis et al 2014 (Hasseler et al 2016). Die jeweilige Performance einer pflegerischen Situation wird jedoch auch durch verschiedene Determinanten außerhalb der methodischen, sozialen und fachlich-kognitiven Kompetenzen konstituiert.…”
Section: Christiane Luderer Und Gabriele Meyerunclassified
“…9,10 This disqualifies the use of standard categories for evaluation since these might not correspond to the values of the individual. 16,17 Third, CE is a political-ethical discipline 9 with ambitions that stretch further than personal relationships, which also pays attention to institutions and systems. It can be deduced that there should be attention not only for the relationship within care ethical evaluation but also for systemic forces and clashing logics and rationalities that are of influence within the institutional context.…”
Section: Introductionmentioning
confidence: 99%
“…Mismatch could be caused by a lack of relational attunement to the needs and wishes of the other, even while medical-technical care is excellent. 17 In a review study, 17 40 instruments were identified based on this operationalization, of which three qualitative instruments appeared most promising for the evaluation of care from a care ethical perspective. In this study, the most promising of these three methods, the emotional touchpoint method, is tested.…”
Section: Introductionmentioning
confidence: 99%